Aboriginal title the modern jurisprudence of tribal land rights - McHugh, Paul G., 1958- (Oxford : Oxford University Press, 2011)
Aboriginal title, the land rights of native peoples in former colonies, is one of the most significant developments in common law in the late 20th century. This book, by a key author in this field, sets out the beginnings, judicial acceptance and influence of this doctrine across national jurisdictions and in international law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Indigenous peoples -- Land tenure; Land tenure -- Law and legislation -- History; Indigenous peoples -- Government relations; Indigenous peoples -- Legal status, laws, etc